2003
DOI: 10.1038/sj.leu.2403224
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3 receptor in acute leukemia

Abstract: Recent studies indicate that abnormalities of the interleukin-3 receptor (IL-3R) are frequently observed in acute myeloid leukemias (AMLs) and may contribute to the proliferative advantage of leukemic blasts. This review analyzes the evidences indicating that the IL-3R represents one of the target molecules involved in the stimulation of proliferation of AMLs, and the overexpression of the IL-3Ra chain may represent one of the mechanisms contributing to the development of a highly malignant leukemic phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 77 publications
2
81
0
1
Order By: Relevance
“…Another possible antigenic target is the CD123 molecule, which encodes the interleukin-3 receptor alpha chain. Several studies have indicated increased CD123 expression in myeloid leukemias (Testa et al, 2004), and one report describes strong expression of CD123 on the LSC population but not on normal HSC (Jordan et al, 2000). The differential expression of CD123 on malignant stem cells makes it a potentially attractive target for therapy.…”
Section: Effects Of Current Therapies On the Lscmentioning
confidence: 99%
“…Another possible antigenic target is the CD123 molecule, which encodes the interleukin-3 receptor alpha chain. Several studies have indicated increased CD123 expression in myeloid leukemias (Testa et al, 2004), and one report describes strong expression of CD123 on the LSC population but not on normal HSC (Jordan et al, 2000). The differential expression of CD123 on malignant stem cells makes it a potentially attractive target for therapy.…”
Section: Effects Of Current Therapies On the Lscmentioning
confidence: 99%
“…Another protein implicated in survival pathways in leukemia is the IL-3 receptor (IL-3R) (Testa et al, 2004). More than 80% of AML samples express IL-3R, and 45% have elevated expression of the IL-3Ra chain compared to normal CD34 þ cells (Budel et al, 1989;Testa et al, 2002).…”
Section: Survivalmentioning
confidence: 99%
“…GM-CSF alone can induce the macrophage differentiation and proliferation [11,12]. IL-3 alone can induce the macrophage activation and proliferation [13]. These cytokines regulate the growth, differentiation, migration and effector function activities of many hematopoietic cells in bone marrow, blood and sites of inflammation.…”
Section: Introductionmentioning
confidence: 99%